2023
DOI: 10.1111/1462-2920.16372
|View full text |Cite
|
Sign up to set email alerts
|

The lignin‐degrading abilities of Gelatoporia subvermispora gat1 and pex1 mutants generated via CRISPR/Cas9

Abstract: White-rot fungi efficiently degrade wood lignin; however, the mechanisms involved remain largely unknown. Recently, a forward genetics approach to identify several genes in Pleurotus ostreatus (Agaricales) in which mutations cause defects in wood lignin degradation was used. For example, pex1 encodes a peroxisome biogenesis factor and gat1 encodes a putative Agaricomycetes-specific DNA-binding transcription factor. In this study, we examined the effects of single-gene mutations in pex1 or gat1 on wood lignin d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…It was reported that in genome-edited strains of P. ostreatus and Gelatoporia subvermispora, , part of the plasmid fragment had been integrated into the target site. Currently, off-target events are often reduced by using computational tools and re-editing the CRISPR components such as Cas proteins and gRNA .…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that in genome-edited strains of P. ostreatus and Gelatoporia subvermispora, , part of the plasmid fragment had been integrated into the target site. Currently, off-target events are often reduced by using computational tools and re-editing the CRISPR components such as Cas proteins and gRNA .…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was extracted from each strain via the cetyl trimethyl ammonium bromide method as described by Muraguchi et al (2003) and Zolan and Pukkila (1986). The extracted DNA ($3 μg) was subject to Southern blot analysis as described by Nakazawa et al (2023). Restriction enzymes to digest genomic DNA and primers to amplify a genomic fragment for a probe were XhoI and TN1022/TN1023 (vp2), PstI and TN1422/TN1423 (vp3), HindIII and BamHI, and TN1426/TN1427 (mnp2), XhoI and TN1430/TN1431 (mnp3), XhoI and TN1424/TN1425 (mnp6), XhoI and TN1428/TN1429 (lac2), respectively.…”
Section: Southern Blot Analysismentioning
confidence: 99%
“…Future studies are required to utilize this technique in functional analyses. Recently, we used a DNA (plasmid)-based method to conduct a functional analysis of genes involved in the sexual development of P. ostreatus 46) and lignin degradation by G. subvermispora 47) . In these cases, the introduced plasmid(s) were randomly integrated into the host chromosomes.…”
Section: Crispr/cas9 In White-rot Fungimentioning
confidence: 99%